A Critical Survey of the Recent Baroque Theories. - Hatzfeld, Helmut (Thesavrvs, 2023)
The excellent criticism on articles concerning the Baroque problem in literature by Rene Wellek, in art by Wolfgang Stechow and in music by Willian Fleming, published together in The Journal of Aesthetics and Art Criticism, V (Dec. 1946), pp. 77-121, has found an unusual repercussion in the Revista de Ideas Estéticas (Madrid), V (1947), pp. 453- 465. The American reviews and their Spanish echo, however, rather offer a picture of the apparent maze of contradictory opinions than a critical separation of the wheat from the chaff. Such a separation seems necessary to make free the path to truly constructive scholarship along the Baroque line.